Solubility of chlorargyrite (AgCl(cr./l.)) in water: New experimental data and a predictive model valid for a wide range of temperatures (273–873 K) and water densities (0.01–1 g·cm−3). (1st April 2016) - Akinfiev, Nikolay N.; Zotov, Alexander V.
Abstract: The solubility of chlorargyrite, AgCl(cr./l.), in pure water at 623, 673 and 753 (±2) K as a function of pressure in a wide range aqueous densities (0.01–0.7 g·cm −3 ) was determined using various experimental approaches. Combined theoretical quantum chemistry simulations of Ag speciation and structure with a recently developed equation of state (EoS) for aqueous neutral species (Akinfiev and Diamond, 2003) were applied to describe published and newly made AgCl(cr./l.) solubility measurements in water. The use of the employed EoS for AgCl(H2 O)(aq) cluster is found out to provide a good description of the whole set of experimental measurements in a wide range of temperatures (273–753 K), water densities (0.01–0.7 g·cm −3 ), and pressures of 0.1–100 MPa. Also, the proposed AgCl(H2 O)(aq) thermodynamic description is proved to be valid for a dense aqueous fluid (0.7–1 g·cm −3 ) at 273–623 K and saturation water pressure. Although silver obviously shows greater affinity to dense aqueous fluid, AgCl hydration in the vapour phase is demonstrated to be also significant. A model extrapolation to magmatic conditions predicts an appreciable silver content even in low density fluids, thus supporting the hypothesis of metal transport with vapour.